Incidence of diverticular disease diagnosed over forty years for colon barium enema. - Arriciaga V, Johana; Cisneros Cañarte, Olga Daniela; Pow Chon Long, Celia María (Revista Universidad de Guayaquil, 2011)
Diverticular disease of the colon is a disease that gradually increases in frequency, which is why we have conducted a study to determine the incidence in the Hospital Teodoro Maldonado Carbo, based on the results obtained in the barium enema Colon (EBC), which performed in 100 patients over 40 years. It was found that 48% of patients enrolled in or beyond the fourth decade of life suffer from diverticulum in the colon. The age group most commonly performed in the EBC was in the sixth decade of life, the latter being the most affected by this disease by 66% and 67% eighth decade. Diverticulum were observed during this study were acquired and the sigmoid colon segment is its location the most common. From what I can conclude is that although colon diverticulum is a disease of developed countries, poor eating habits, Ecuador presents similar incidents and this grows with increasing longevity of populations and one of the factors responsible for the intake low in fiber has been replaced by foods that are placed on top of the food pyramid. We recommend a change in dietary habits as well as prevalence increases, the risks grow.